Biometrics Authentication of Fingerprint with Using Fingerprint Reader and Microcontroller Arduino - Magdin Martin; Koprda Štefan; Ferenczy Ľubor (Universitas Ahmad Dahlan, 2018)
The idea of security is as old as humanity itself. Between oldest methods of security were included simple mechanical locks whose authentication element was the key. At first, a universal–simple type, later unique for each lock. A long time had mechanical locks been the sole option for protection against unauthorized access. The boom of biometrics has come in the 20th century, and especially in recent years, biometrics is much expanded in the various areas of our life. Opposite of traditional security methods such as passwords, access cards, and hardware keys, it offers many benefits. The main benefits are the uniqueness and the impossibility of their loss. The main benefits are the uniqueness and the impossibility of their loss. Therefore we focussed in this paper on the the design of low cost biometric fingerprint system and subsequent implementation of this system in praxtise. Our main goal was to create a system that is capable of recognizing fingerprints from a user and then processing them. The main part of this system is the microcontroller Arduino Yun with an external interface to the scan of the fingerprint with a name Adafruit R305 (special reader). This microcontroller communicates with the external database, which ensures the exchange of data between Arduino Yun and user application. This application was created for (currently) most widespread mobile operating system-Android.